Role of endocannabinoid signalling in the dorsolateral periaqueductal grey in the modulation of distinct panic-like responses. (March 2015) - Batista, Luara A; Bastos, Juliana R; Moreira, Fabricio A
Panic attacks, a major feature of panic disorder, can be modelled in rats by exposing animals to stimuli that induce escape reactions, such as the elevated T-maze or the activation of the dorsolateral periaqueductal grey. Since the cannabinoid CB1 receptor modulates various types of aversive responses, this study tested the hypothesis that enhancement of endocannabinoid signalling in the dorsolateral periaqueductal grey inhibits panic-like reactions in rats. Local injection of the CB1 agonist, arachidonoyl 2-Chloroethylamide (0.005–0.5 pmol), attenuated the escape response from the open arm of the elevated T-maze, a panicolytic effect. The anandamide hydrolysis inhibitor, URB597 (0.3–3 nmol), did not induce consistent results. In the test of dorsolateral periaqueductal grey stimulation with d, l-homocysteic acid, arachidonoyl 2-Chloroethylamide, at the lowest dose, attenuated the escape reaction. The highest dose of URB597 also inhibited this response, contrary to the result obtained in the elevated T-maze. This effect was reversed by the CB1 antagonist, AM251 (100 pmol). The present results confirm the anti-aversive property of direct CB1 receptor activation in the dorsolateral periaqueductal grey. The effect of the anandamide hydrolysis inhibitor, however, could be detected only in a model employing direct stimulation of this structure. Altogether, these results suggest that anandamide signalling is recruited only under certain types of aversive stimuli.